(untitled) (Mustansiria Dental Journal, 2022)
Background/ Aims: High bond strength of root perforation repair materials is essential for success of endodontic therapy. The aims of current study were to assist the push-out bond strength of 4 types of root perforation repair materials (Biodentine , Mineral trioxide aggregate, glass ionomer cement, and calcium hydroxide paste) from dentin, and to determine the modes of failure at debonded surfaces. Materials and Methods: Forty lower premolars with a straight single root canal and matured apex were utilized. Then the teeth decorated 15 mm from the apex, and the middle third of the roots were cut perpendicular to their long axis in order to obtain sections with 1 mm thick. After that instrumentation for the canal of the dentin discs with Gates Glidden was done from sizes 2-5 to result into standardized cavities with 1.3 mm diameter. After that, specimens were divided randomly into 4groups with 10 specimens in every group as follows: group I: Bio (Biodentine), group II: Mineral trioxide aggregate ( MTA), group III: GI (glass ionomer), and group IV: calcium hydroxide paste (Ca(OH)2). Prepared cavity was then filled with each of the material tested according to the corresponding groups. after setting of the tested materials the specimens stored for one week and then push-out bond strength test preformed. Results: push-out bond strength of Biodentine was significantly higher than other tested materials. Followed by Mineral trioxide aggregate, which exhibited significantly higher bond strength than glass ionomer and MTA materials, while the Ca(OH)2 showed the lowest value of push-out bond strength. Conclusions: push-out bond strength Biodentine, was significantly greater than MTA, GI, and Ca(OH)2. Therefore, BIO can be used successfully for treatment of root perforation that might occur during endodontic therapy of the root canal.